Social responses to climate change in Iron Age north-east Thailand: new archaeobotanical evidence. (26th October 2018) - Castillo, Cristina C.; Higham, Charles F.W.; Miller, Katie; Chang, Nigel; Douka, Katerina; Higham, Thomas F.G.; Fuller, Dorian Q
Abstract : Abstract : New evidence from archaeological investigations in north-east Thailand shows a transition in rice farming towards wetland cultivation that would have facilitated greater yields and surpluses. This evidence, combined with new dates and palaeoclimatic data, suggests that this transition took place in the Iron Age, at a time of increasingly arid climate, and when a number of broader societal changes become apparent in the archaeological record. For the first time, it is possible to relate changes in subsistence economy to shifts in regional climate and water-management strategies, and to the emergence of state societies in Southeast Asia.